Teaching gender equality in teacher education: does existing practice actually support gender mainstreaming implementation? - Miralles-Cardona, Cristina (Frontiers in Education, 2025)
IntroductionGender equality in education remains a global priority and a key component of sustainable development. However, its integration into teacher education programs is still inconsistent. The absence of gender-responsive education constitutes a major barrier to achieving gender equality. This study investigates the extent to which gender-responsive pedagogy is incorporated into teacher education at the University of Alicante, with a focus on the teaching content and methods employed by faculty and their impact on pre-service teachers’ self-efficacy for gender-responsive practice.MethodsA descriptive cross-sectional survey was conducted with 161 pre-service teachers at the University of Alicante. Data were collected using validated scales measuring gender-responsive teaching and teacher efficacy for gender equality practice.ResultsFindings revealed that gender-related topics are only moderately integrated into coursework, with content primarily focused on gender-based violence and equal opportunities, while foundational gender concepts receive little attention. Teaching methods largely rely on traditional approaches, such as lectures and project-based learning, rather than interactive or inquiry-based strategies. Pre-service teachers who had received gender training reported higher perceived self-efficacy in gender pedagogy; however, no statistically significant differences were observed in overall competence levels.DiscussionThe results point to a limited institutional commitment to gender mainstreaming in teacher education and underscore the need for comprehensive reforms, including curriculum revision, faculty training, and stronger institutional accountability to advance meaningful gender equality in education.